Judicial Control on Administration Deviation within Administrative Decisions: The Case of UAE - Alshawabkeh, Faisal Abed Alhafaz; Alshawabkeh, Faisal Abed Alhafaz; Alteneji, Abdulla Abdul Rahman (International Journal of Psychosocial Rehabilitation, 2020)
Judicial control is an effective means to protect individual’s rights and freedom from the iniquity and arbitrariness of administration power. The present study has addressed the subject matter of judicial control on administration deviation within administrative decisions in United Arabs Emirates (UAE). This study has been divided into three themes where in the first theme the concept of deviation of power is addressed. While, the second theme has addressed the cases of deviation of power and the third theme illustrated how to substantiate administration deviation with power. The study concluded that the concept deviation of power is a hidden defect strongly connected with psychological intents of the administrative decision maker. Therefore, it among the most difficult to prove by an administrative judge. The study finally provided certain recommendations.